STRATEGI PENILAIAN KOGNITIF ANAK OLEH PENDIDIK PAUD PELITA KASIH SAAT PANDEMI COVID-19 - I Komang Sesara Ariyana; Komang Trisna Mahartini; Ni Putu Widyasanti (Institut Pendidikan Tapanuli Selatan, 2021)
This study aimed to determine the cognitive assessment strategy of children by educators at PAUD Pelita Kasih Singaraja during the Covid-19 pandemic. The research site is located in Buleleng District, Buleleng Regency, Bali Province. This study used a qualitative descriptive method. The techniques of collecting research data were by conducting interviews and documentation. The research subjects were two teachers, namely the homeroom teacher of TK A and the homeroom teacher of TK B, including the principal. Interviews were conducted by positioning the researcher as the main instrument assisted by interview guidelines with interview guidelines to obtain primary data. Documentation was carried out to obtain other supporting data as secondary. The results showed that the assessment strategy used by PAUD Pelita Kasih was to provide a holistic assessment through process assessment and outcome assessment during the Covid-19 pandemic. Process assessment was carried out when learning was face-to-face, either virtually by using the Zoom meeting application or directly by conducting a home visit. Face-to-face activities, both virtual and in-person, were each held once a week. Educators stated that students' cognitive aspects were developing well as before pandemic. This was due to the trust and support of parents, both directly and indirectly, so that the assessment given by educators was also good for their students.